Immunomodulatory properties of Trehala manna decoction and its isolated carbohydrate macromolecules. (13th March 2015) - Hamedi, Azadeh; Farjadian, Shirin; Karami, Mohammad Reza
Abstract: Ethnopharmacological relevance: Trehala manna ( Shekar tighal ) is a cocoon-shaped manna produced by larval activity of Curculionidae family on some Echinops species. In Persian traditional medicine, it is used not only for the treatment of fever and constipation but also for sore throat, influenza and some other viral and bacterial infections which seems to be related to its boosting effects on immune system. The aim of this study was to evaluate immunomodulatory properties of Trehala manna and its isolated polysaccharides. Materials and methods: Several carbohydrate macromolecules were isolated from Trehala manna decoction using solvent–solvent extraction, ion exchange and size-exclusion chromatography. The macromolecules were characterized by gas chromatography–mass spectrometry and spectrophotometric methods. The immunomodulatory effects of Trehala manna decoction and its isolated polysaccharides were evaluated on Jurkat cells at different concentrations using WST-1 reagent. Results: Seven water-soluble polysaccharides were isolated with the structures of rhamnogalacturonan, glucogalacturonan, manno-arabinogalacturonan or homogalacturonan and the molecular weights (MW) of ≤1.67–667≤ kDa. Large polysaccharides with MW ≥667 kDa and pectin inhibited the proliferation of Jurkat cells in a dose-dependent manner with the IC50 range of 98.06–429.53 µg/mL. The IC50 for low MW polysaccharides (around 1 kDa) did not show considerable cytotoxicity (IC50 >1000 µg/mL), in contrast, they exhibited a dose-dependent enhancement of cell proliferation at concentration range of 15.62–62.50 μg/mL. Conclusion: Trehala aqueous decoction and its isolated polysaccharides showed some immunomodulatory effects on Jurkat cell line in a dose-dependent manner and the molecular weight of these polysaccharides also revealed a great impact on their cytotoxic/proliferative properties. Graphical abstract: